Mitophagy during development and stress in C. elegans. (July 2020) - Leboutet, Romane; Chen, Yanfang; Legouis, Renaud; Culetto, Emmanuel
Highlights: Ubiquitin dependent and ubiquitin independent pathways participate to the selective degradation process of mitochondria by mitophagy. The model organism C. elegans has emerged as a leading animal to study the physiological role of mitophagy. Multiple mechanisms including mitophagy, participate to the elimination of paternal mitochondria. The transcription factor SKN-1/Nrf2 coordinates mitochondrial biogenesis and mitophagy during C. elegans aging and stress. C. elegans models are used to study the role of mitophagy in neurodegenerative diseases. Abstract: Mitochondria is a key cellular organelle, which is tightly supervised by multiple oversight cellular mechanisms regulating mitochondrial biogenesis and mitochondria maintenance and/or elimination. Selective autophagy of mitochondria, id est mitophagy, is one of the cellular mechanisms controlling mitochondria homeostasis. The nematode Caenorhabditis elegans has recently emerged as a powerful model organism to study the roles and functions of mitophagy. We present here the current knowledge on cellular and molecular mechanisms underlying the selective elimination of mitochondria by autophagy in C. elegans in the context of developmental processes, aging and adaptive responses to various stresses.